Identifying Triggers of Alcohol Craving to Develop Effective Virtual Environments for Cue Exposure Therapy - Ghiţă, Alexandra; Teixidor, Lidia; Monras, Miquel; Ortega, Lluisa; Mondon, Silvia; Gual, Antoni; Paredes, Sofia Miranda; Villares Urgell, Laura; Porras-García, Bruno; Ferrer-García, Marta; Gutiérrez-Maldonado, José (Frontiers in Psychology, 2019)
Background: Many studies have indicated that alcohol craving is a core mechanism in the acquisition, maintenance, and precipitation of relapse in alcohol use disorder (AUD). A common treatment approach in AUD is cue exposure therapy (CET). New technologies like virtual reality (VR) have the potential to enhance the effectiveness of CET by creating realistic scenarios in naturalistic environments. In this study, we aimed to determine relevant triggers of alcohol craving in patients with AUD. Method: We enrolled 75 outpatients diagnosed with AUD according to the DSM-5 criteria Participants completed the Alcohol Use Disorder Identification Test and a self-administered questionnaire to assess alcohol craving. The variables included in the craving questionnaire were as follows: presence of others, situations, time of the day, day of the week, mood, and type of alcoholic beverage. Results: Greater levels of alcohol craving were seen in many situations, including being at a party, in a restaurant, in a bar or pub, and at home. Drinking alone and drinking with two or more friends were equally associated with higher levels of craving. Drinking at night and drinking at weekends also emerged as triggers for alcohol craving. Emotional states like anxiety or tension, sadness, stress, frustration, or irritability were highly associated with urges to drink alcohol. The alcoholic drinks most highly associated with increased levels of craving were beer, wine, and whisky. Gender and age implications were discussed. Conclusions: This study is part of a larger project aiming to develop and validate CET based on VR technology for patients with AUD who are resistant to classical treatment. The identified triggers have been used to develop relevant VR environments for CET, and further research is ongoing to implement our findings.